Modelling of flaky particle motion under typical vibration excitation for gas insulated switchgear live operation - Jian Wang; Chengyi Qin; Teng Zhang; Keda Chen; Yuyi Wu; Hao Wang; Hanwen Ren; Qingmin Li (High Voltage)
Abstract Within 30 min after live operation of gas‐insulated switchgear (GIS), more than 60% of discharge failures are caused by metallic particles. To address this issue, this study explored the vibration propagation mechanisms in GIS cavities and established an equivalent vibration transmission model. A kinetic energy transfer conservation model between the cavity and particles was constructed, systematically analyzing the critical factors affecting the particle starting field strength and explicitly formulating the criterion for vibration‐induced particle activation. The electric field distortion caused by particle rotation was investigated, and a collision dynamics model characterizing rotational motion was developed. By analyzing the critical conditions for stable and rotational motion, the corresponding criterion was derived. The results showed that the electric field distortion caused by flaky particles increases with the rotation angle. Vibration effectively activates particles and enhances their mobility. The discharge risk is positively correlated with vibration intensity and particle thickness, but negatively correlated with particle size. This paper clarifies the motion mechanism of flaky metal particles in GIS under shock vibration, providing support for solving the problem of frequent faults after GIS live operation.